Improved slit-shaped microseparator and its integration with a microreactor for modular biomanufacturing. Issue 10 (7th May 2021) - Bhattacharyya, Souryadeep; Desir, Pierre; Prodinger, Sebastian; Lobo, Raul F.; Vlachos, Dionisios G.
Abstract : Pictures of microseparator parts and integrated microreactor and microseparator to produce high purity streams containing platform biomass-derived chemicals. Abstract : Modular and distributed biomanufacturing requires continuous flow microreactors integrated with efficient separation units operating at comparable time scales: biphasic reactive extraction of 5-hydroxymethyl furfural (HMF) by fructose dehydration is an excellent example. The liquid–liquid extraction (LLE) and fast reaction kinetics in biphasic microchannels can immensely benefit from a downstream microseparator enabling separation of an HMF-rich organic extract and an aqueous raffinate. Here we demonstrate the successful implementation of an effective slit-shaped microseparator for eleven organic-water biphasic systems. The microseparator successfully separates six of these over reasonable flow rates. The ratio of capillary and hydraulic pressures qualitatively rationalizes the separation performance, while a transition to non-segmented flow patterns correlates with performance deterioration. Acids and salts, integral parts of the chemistry, significantly expand the flow rates for efficient separation enabling a broader slate of organic solvents. For the MIBK/water biphasic system, we demonstrate perfect separation performance over a 16-fold variation in the organic to aqueous flow ratio. Here we also integrate the microseparator and extractive microreactor into a modular system and achieve an HMF yield of up to 93% – the highest reported fractional HMF productivity of 27.9 min −1 – at an ultrashort residence time of 2 s. This unprecedented performance is maintained over a 50-fold fructose concentration range and is stable with time-on-stream. This microseparator exhibits a ten-fold reduction in separation time and substantial energy savings over conventional decanters. As such, it holds promise for continuous process intensification and modular biomanufacturing.